2022
DOI: 10.4012/dmj.2021-318
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of a glass ionomer cement containing fluoro-zinc-silicate glass on dentin remineralization using the ultrasonic pulse-echo method

Abstract: The purpose of this study was to investigate the protective effect of a glass ionomer cement (GIC) consisting of fluoro-zinc-silicate glass on the demineralization of bovine dentin using the ultrasonic pulse-echo method. The findings were compared with those obtained using a conventional GIC. Slabs of dentin from bovine teeth were sliced, shaped into a rectangular form, and immersed in 0.5 M ethylenediaminetetraacetic acid solution at 25ºC for 6 days, followed by storage in distilled water for 3 days. After de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Finally, DW was used as a negative control. The pH of WT (5.011 ± 0.038), which was below 6.0, the critical pH of dentin [ 22 , 23 ], was sub-acidic in contrast to CT, RS, SPDS, and DW in the present study (Table 1 ).…”
Section: Discussionmentioning
confidence: 44%
“…Finally, DW was used as a negative control. The pH of WT (5.011 ± 0.038), which was below 6.0, the critical pH of dentin [ 22 , 23 ], was sub-acidic in contrast to CT, RS, SPDS, and DW in the present study (Table 1 ).…”
Section: Discussionmentioning
confidence: 44%
“…Numerous studies have reported on the effects of BioUnion filler GIC, notably its ability to inhibit biofilm formation 14,16,[32][33][34] . Additionally, zinc ions, like fluoride ions, have been demonstrated to permeate the dentin 35) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, remineralisation of caries-affected dentin has been described adjacent to modified GICs or other ion-releasing materials, including antibacterial fillers. 15 , 18 However, remineralisation of dentin cannot be considered only as a chemical deposition of apatite. Other factors, such as the collagen fibrils, play an essential role, and substances like tannic acid for crosslinking collagen fibrils also interact chemically with dentinal tissues to improve remineralisation.…”
Section: Target Tissues and Aimsmentioning
confidence: 99%